Capture, Storage, and Release of Oxygen by Metal–Organic Frameworks (MOFs). Issue 37 (4th August 2022) - Sutton, Ashley L.; Melag, Leena; Sadiq, M. Munir; Hill, Matthew R.
Abstract: Oxygen is a critical gas for medical and industrial settings. Much of today's global oxygen supply is via inefficient technologies such as cryogenic distillation, membranes or zeolites. Metal–organic frameworks (MOFs) promise a superior alternative for oxygen separation, as their fundamental chemistry can in principle be tailored for reversible and selective oxygen capture. We evaluate the characteristics for reversible and selective uptake of oxygen by MOFs, focussing on redox‐active sites. Key characteristics for separation can also be seen in MOFs for oxygen storage roles. Engineering solutions to release adsorbed oxygen from the MOFs are discussed including Temperature Swing Adsorption (TSA), Pressure Swing Adsorption (PSA) and the highly efficient Magnetic Induction Swing Adsorption (MISA). We conclude with the applications and outlooks for oxygen capture, storage and release, and the likely impacts the next generation of MOFs will have on industry and the broader community. Abstract : Metal–organic frameworks (MOFs) are emerging materials for oxygen capture and storage with significant benefits for the broader community. This Minireview assesses and discusses the fundamental chemistry for both selective and reversible MOFs for the role of oxygen capture from air. In addition, we describe the current state of play for oxygen storage by MOFs, as well as engineering solutions to aid in the release of oxygen once captured.